Optimization of teaching quality of college physical education by using decision making technique under complex interval valued fermatean fuzzy model - Duo Huang; Yangjun Liu (Scientific Reports)
Abstract Teaching quality in college physical education (PE) promotes students’ overall physical and mental development. Improving this quality thus entails assessing mainly intrinsically complex variables that tend to include probabilities and subjective factors. This paper develops a new decision-making framework to enhance the quality of college PE teaching through a Complex Interval-Valued Fermatean Fuzzy Dombi Aggregation (CIVFFDA) Operator. The objective framework incorporates differentiated criteria, such as instructor competence, student activity level, the quality of facilities, and teaching performance during several PE course options. Using complex interval-valued Fermatean fuzzy sets (CIVFFS), this model incorporates the fuzziness and hesitancy inherent in experts’ evaluations of teaching activity quality, providing a more comprehensive representation. The Dombi aggregation operator is applied for the evaluation aggregation, so the relative importance of the criteria is appropriately reflected. This paper’s findings illustrate the effectiveness of employing fuzzy sets (FS) in supporting the decision to select exemplary teaching practices that foster college PE improvement. Therefore, this study benefits the decision-making process for maximizing educational quality and offers suggestions for enhancing PE to administrators and educators.